Self-sensing engineering cement-based composite material as well as preparation method and application thereof
By introducing conductive carbon materials into engineering cement matrix composites to form a conductive network, the problem of traditional structural health monitoring technology relying on external sensors is solved, real-time monitoring of structural stress and strain is achieved, and the advantages of low cost, wide range, and anti-environmental interference are achieved.
Patent Information
- Application Number
- CN202510019301.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional structural health monitoring technology relies on external sensors, and has problems such as high installation costs, limited monitoring range, and susceptibility to environmental impact.
Develop a self-perception engineering cement-based composite material that forms a conductive network by introducing conductive carbon materials into the material to achieve real-time monitoring of structural stress and strain without external sensors.
Real-time monitoring of stress and strains of building materials and structures is achieved, with low cost, wide monitoring range, not easily affected by the environment, and has self-perception functions.
Smart Images

Figure CN119797863A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cement-based materials, and in particular relates to a self-sensing engineering cement-based composite material and a preparation method and application thereof. Background Art
[0002] Structural Health Monitoring (SHM) is a specific application of fault prediction and health management (PHM) technology in the field of structures. Initially, it mainly monitored structural loads. Now it is developing towards structural damage monitoring, damage location, and structural life prediction, and is gradually developing into the function of self-repair and self-protection of structural damage.
[0003] Traditional SHM technology mainly installs various external sensors in the structure or on its surface to monitor the physical parameters of the structure such as stress, strain, displacement, vibration, etc. in real time to evaluate the health of the structure. These sensors usually include accelerometers, strain gauges, displacement gauges, vibration sensors, etc., which are installed in key parts of the structure such as beams, columns, walls, etc. Traditional SHM technology relies on external sensors, and has problems such as high installation cost, limited monitoring range, and susceptibility to environmental influences. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a self-sensing engineering cement-based composite material and a preparation method and application thereof. The engineering cement-based composite material has a self-sensing function, and its electrical conductivity can respond to changes in the mechanical behavior of the structure. Without the need for external sensors, real-time monitoring of the stress and strain of building materials and structures can be achieved.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a self-sensing engineering cement-based composite material, comprising an engineering cement-based composite material and a conductive carbon material; the raw materials for preparing the engineering cement-based composite material include a cementitious material, an aggregate, an organic fiber, a water reducing agent, a dispersant and water; the cementitious material includes cement, mineral powder, silica fume and limestone powder;
[0007] The conductive carbon material includes one or more of carbon black, carbon nanotubes and graphene;
[0008] The mass of the conductive carbon material is 0.5-2.5% of the mass of the cement.
[0009] Preferably, the carbon black has a diameter of 27 to 40 nm and an apparent density of 0.06 to 0.11 cm 3 / g, specific resistance ≤1.5Ω·m, pH value is 6-8, and apparent specific volume is 15-18mL / g.
[0010] Preferably, the organic fibers include polyester fibers and / or polyethylene fibers; the volume fraction of the organic fibers in the self-sensing engineering cement-based composite material is 1 to 2%; the length of the organic fibers is 15 to 20 mm, and the diameter is 20 to 25 μm.
[0011] Preferably, the dispersant includes one or more of povidone, carboxymethyl fiber and sodium polyacrylate; the amount of the dispersant added to the self-sensing engineering cement-based composite material is 0.5-1 kg / m 3 .
[0012] Preferably, the water reducer includes one or more of a polycarboxylate water reducer, a naphthylamine water reducer and a lignin sulfonate water reducer; the amount of the water reducer added to the self-sensing engineering cement-based composite material is 20 to 45 kg / m 3 .
[0013] Preferably, the mass ratio of water to gelling material is 0.16-0.24:1.
[0014] Preferably, the mass ratio of the cement, mineral powder, silica fume and limestone powder is 1:1-1.1:0.2-0.3:0.1-0.15; the mass ratio of the cement and aggregate is 1:0.7-0.8.
[0015] The present invention also provides a method for preparing the self-sensing engineering cement-based composite material described in the above technical solution, comprising the following steps:
[0016] The self-sensing engineering cement-based composite material is obtained by mixing a cementitious material, an aggregate, a conductive carbon material, an organic fiber, a water reducing agent, a dispersant and water.
[0017] The present invention also provides the use of the self-sensing engineering cement-based composite material described in the above technical solution or the self-sensing engineering cement-based composite material prepared by the preparation method described in the above technical solution in structural health monitoring.
[0018] The present invention also provides a method for structural health monitoring, comprising the following steps: connecting two end electrodes of a self-sensing area in a building structure to a resistance meter with wires to obtain resistivity, and obtaining stress and / or strain according to the resistivity and the linear relationship between the resistivity and the stress and / or strain;
[0019] The raw material for preparing the self-sensing area is the self-sensing engineering cement-based composite material described in the above technical solution or the self-sensing engineering cement-based composite material prepared by the preparation method described in the above technical solution.
[0020] The present invention provides a self-sensing engineering cement-based composite material including an engineering cement-based composite material and a conductive carbon material; the raw materials for preparing the engineering cement-based composite material include a cementitious material, an aggregate, an organic fiber, a water reducer, a dispersant and water; the cementitious material includes cement, mineral powder, silica fume and limestone powder; the conductive carbon material includes one or more of carbon black, carbon nanotubes and graphene; the mass of the conductive carbon material is 0.5-2.5% of the mass of the cement. The conductive carbon material can form a conductive network in the self-sensing engineering cement-based composite material, thereby improving its conductivity and giving it a self-sensing function, and establishing a relationship between stress or strain and the rate of change of resistivity. This process can be summarized as follows: (1) During loading: under the action of stress, the relative positions of the conductive carbon materials change, causing changes in the conductive network. Generally, a larger stress will lead to an increase in contact between the particles of the conductive carbon material and a decrease in resistance; while a smaller stress or deformation will lead to a decrease in contact between the particles of the conductive carbon material and an increase in resistance. (2) Relationship between strain and resistance: Strain (especially tensile strain) can cause microstructural changes in self-sensing engineering cement-based composite materials, especially the breaking or reconnection of the conductive carbon material network, which will cause changes in resistance. By accurately measuring the change in resistance, the magnitude of the strain can be reflected, thereby achieving real-time monitoring of the stress and strain of building materials and structures. The self-sensing engineering cement-based composite material provided by the present invention has a self-sensing function, does not need to rely on external sensors, has low cost, a wide monitoring range, and is not easily affected by the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of an application scenario of the self-sensing engineering cement-based composite material prepared by the present invention;
[0022] Figure 2 This is a schematic diagram of a process for preparing a self-sensing engineering cement-based composite material according to an embodiment of the present invention;
[0023] Figure 3 The compressive strength graph and density graph of the cement-based composite materials prepared in Examples 1 to 5 and Comparative Example 1;
[0024] Figure 4 The tensile properties test diagram of the cement-based composite materials prepared in Examples 1 to 5 and Comparative Example 1;
[0025] Figures 5 to 8 These are compression self-sensing performance test diagrams of cement-based composite materials prepared in Comparative Example 1, Example 1, Example 3 and Example 4, respectively;
[0026] Figures 9 to 12 The tensile self-sensing performance test diagrams of the cement-based composite materials prepared in Comparative Example 1, Example 1, Example 3 and Example 4 are respectively. DETAILED DESCRIPTION
[0027] The present invention provides a self-sensing engineering cement-based composite material, comprising an engineering cement-based composite material and a conductive carbon material; the raw materials for preparing the engineering cement-based composite material include a cementitious material, an aggregate, an organic fiber, a water reducing agent, a dispersant and water; the cementitious material includes cement, mineral powder, silica fume and limestone powder;
[0028] The conductive carbon material includes one or more of carbon black, carbon nanotubes and graphene;
[0029] The mass of the conductive carbon material is 0.5-2.5% of the mass of the cement.
[0030] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0031] The self-sensing engineering cement-based composite material provided by the present invention includes an engineering cement-based composite material; the raw materials for preparing the engineering cement-based composite material include cementitious material, aggregate, organic fiber, water reducer, dispersant and water; the cementitious material includes cement, mineral powder, silica fume and limestone powder.
[0032] As an embodiment, the cement includes one or more of Portland cement, sulphoaluminate cement and ferroaluminate cement, and in the specific embodiment, it is Portland cement; the Portland cement is 52.5R grade ordinary Portland cement; the particle size distribution of the cement is 1 to 300 μm, and in the specific embodiment, it is 20 to 200 μm.
[0033] The type of cement affects the basic mechanical properties and durability of self-sensing engineering cement-based composites. Cement particles with smaller particle sizes help improve the density and uniformity of self-sensing engineering cement-based composites, which may improve the self-sensing performance. The amount of cement is directly related to the strength and toughness of self-sensing engineering cement-based composites. The right amount of cement can ensure that the self-sensing engineering cement-based composites have sufficient compressive and tensile strength. These properties of cement work together on the conductive network in the self-sensing engineering cement-based composites, affecting its real-time monitoring ability of self-stress and strain. For example, silicate cement is often used to improve the mechanical properties of self-sensing engineering cement-based composites due to its good hydration reaction and strength development. The rapid hardening characteristics of sulphoaluminate cement may help control the development of cracks, thereby affecting the self-sensing performance. The heat resistance and corrosion resistance of ferroaluminate cement may improve the durability and self-sensing ability of self-sensing engineering cement-based composites in special environments (such as high temperature environments or corrosive environments).
[0034] As an embodiment, the particle size distribution of the mineral powder is 1 to 50 μm, and in a specific embodiment, it is 5 to 30 μm; the mineral powder is S95 grade granulated blast furnace slag (GGBFS); the density of the S95 grade granulated blast furnace slag is 3100 kg / m 3 , with a specific surface area of 432m 2 / kg. The mineral powder (GGBFS) effectively improves the toughness and crack resistance of the self-sensing engineering cement-based composites by enhancing the durability of the self-sensing engineering cement-based composites and synergizing with other components.
[0035] The role of mineral powder in the self-sensing engineering cement-based composite material in the present invention mainly includes the following points: (1) Mechanical properties: The type and amount of mineral powder affect the compressive strength and tensile strength of the self-sensing engineering cement-based composite material. For example, granulated blast furnace slag can improve the toughness and later strength of the self-sensing engineering cement-based composite material. (2) Self-sensing performance: The particle size and distribution of mineral powder may affect the dispersion of conductive carbon materials (such as carbon black) and the formation of conductive networks. Mineral powder with smaller particle size may help to form a more uniform conductive network, thereby improving the self-sensing performance. (3) Crack control: The addition of mineral powder can improve the crack control ability of the self-sensing engineering cement-based composite material. The appropriate amount of mineral powder helps to control the width and number of cracks, thereby improving its self-sensing performance. (4) Durability: The type and amount of mineral powder also affect the durability of the self-sensing engineering cement-based composite material, including impermeability and chemical corrosion resistance. For example, the addition of granulated blast furnace slag can improve the durability of the self-sensing engineering cement-based composite material. (5) Conductivity: The particle size and distribution of mineral powder may affect the uniformity and continuity of the conductive network, thereby affecting the conductivity and self-sensing properties of self-sensing engineering cement-based composites.
[0036] As an embodiment, the apparent density of the silica fume is 2000-2500 kg / m 3 , in the specific embodiment, 2300kg / m 3 ; The particle size distribution of the silica fume is 1 to 100 μm, and in the specific embodiment it is 10 to 50 μm.
[0037] As an ultrafine particle, silica fume (SF) can fill the pores between aggregates, significantly improve the density of self-sensing engineering cement-based composite materials, and strengthen the continuity of the conductive network, which helps to improve the crack resistance of self-sensing engineering cement-based composite materials. In addition, the mechanical effect of silica fume during the mixing process can effectively promote the dispersion of organic fibers, so that the reinforcing effect of organic fibers can be fully exerted.
[0038] As an implementation method, the particle size distribution of limestone powder is 1 to 20 μm, and in a specific embodiment, 5 to 15 μm. The introduction of limestone powder (LP) can not only reduce the cost of the raw materials for preparing the self-sensing engineering cement-based composite material, but also improve its fluidity, which plays an important role in the uniform dispersion of carbon black.
[0039] As an implementation mode, the mass ratio of the cement, mineral powder, silica fume and limestone powder is 1:1-1.1:0.2-0.3:0.1-0.15, and in a specific embodiment, it is 1:1.07:0.21:0.14.
[0040] As an implementation method, the mass ratio of cement to aggregate is 1:0.7-0.8, and in a specific embodiment, it is 1:0.71; the aggregate includes quartz sand; the particle size of the quartz sand ranges from 10 to 300 μm, and in a specific embodiment, it is 20 to 200 μm. The aggregate provides the necessary rigid support, further improving the mechanical strength of the self-sensing engineering cement-based composite material.
[0041] As an embodiment, the volume fraction of organic fibers in the self-sensing engineering cement-based composite material is 1-2%, and in a specific embodiment, it is 1.5-2%; the length of the organic fibers is 15-20 mm, and in a specific embodiment, it is 16-18 mm, and the diameter is 20-25 μm, and in a specific embodiment, it is 22-24 μm.
[0042] As an embodiment, the organic fiber includes polyester fiber and / or polyethylene fiber (PE), and in a specific embodiment, the organic fiber is polyethylene fiber; the concentration of the polyethylene fiber is 0.97-0.98 g / cm 3 , tensile strength is 3.0GPa, tensile modulus is 116GPa, melting limit is 144~152℃, and elongation at break is 1~3%.
[0043] Organic fiber fibers have high elastic modulus and high tensile strength, which greatly enhance the toughness and tensile strength of self-sensing engineering cement-based composite materials, improve their ductility, and enable multiple cracking. Ordinary concrete has only one main crack when it is damaged by tension, while self-sensing engineering cement-based composite materials can open multiple small cracks due to the addition of fibers, thereby increasing the ductility of the material and laying the foundation for its tensile self-sensing performance.
[0044] As an embodiment, the water reducer includes one or more of a polycarboxylate water reducer, a naphthylamine water reducer and a lignin sulfonate water reducer, and in a specific embodiment, a polycarboxylate water reducer; the addition amount of the water reducer in the self-sensing engineering cement-based composite material is 20 to 45 kg / m 3 , in the specific embodiment, 25 to 40 kg / m 3 .
[0045] The role of the water reducer in the self-sensing engineering cement-based composite material in the present invention mainly includes the following points: (1) Improving workability: The water reducer can reduce the moisture content in the cement paste while maintaining or improving its fluidity, making construction more convenient. (2) Reducing water consumption: By reducing the water-cement ratio, the water reducer helps to reduce the porosity in the cement paste, thereby improving the density and strength of the material. (3) Improving strength: The appropriate use of water reducers can improve the compressive strength and impermeability of cement-based materials. (4) Enhancing durability: The water reducer helps to reduce the porosity of the cement paste, thereby improving the durability of the material and reducing cracks and penetration. (5) Improving self-sensing performance: In the self-sensing engineering cement-based composite material, the water reducer helps to improve its self-sensing performance by improving the density and uniformity of the material, making the material more sensitive to stress and strain monitoring.
[0046] As an embodiment, the dispersant includes one or more of polyvinylpyrrolidone (PVP-K30), carboxymethyl fiber and sodium polyacrylate, and polyvinylpyrrolidone is used in the specific embodiment; the molecular weight of the polyvinylpyrrolidone is 30000-50000Da, and 40000Da is used in the specific embodiment; the addition amount of the dispersant in the self-sensing engineering cement-based composite material is 0.5-1kg / m 3 , in the specific embodiment, 0.5kg / m 3 .
[0047] The main function of the dispersant in the present invention is to coat the surface of the conductive carbon material particles to prevent the particles from agglomerating and ensure the stability of the dispersion. A good dispersion effect can ensure that the conductive carbon material particles are evenly distributed in the cement matrix to form an effective conductive network, thereby improving the uniformity and conductivity of the self-sensing engineering cement-based composite material, and further improving its self-sensing performance, including real-time monitoring of stress and strain.
[0048] As an implementation mode, the mass ratio of water to gelling material is 0.16-0.24:1, and in a specific embodiment, it is 0.18-0.22:1.
[0049] The water-binder ratio is the mass ratio of water to cementitious materials, which is water / (cement + mineral powder + silica fume + limestone powder). The effects of the water-binder ratio on self-sensing engineering cement-based composites are as follows: (1) Workability: A lower water-binder ratio can improve the fluidity and workability of self-sensing engineering cement-based composites, making them easier to construct and shape. However, a too low water-binder ratio may cause the self-sensing engineering cement-based composites to be too viscous and difficult to construct. (2) Strength: An appropriate water-binder ratio helps to fully hydrate cement particles, thereby improving the compressive and tensile strength of self-sensing engineering cement-based composites. Too high or too low a water-binder ratio may be detrimental to the development of strength. (3) Self-sensing performance: The water-binder ratio affects the formation of a conductive network in self-sensing engineering cement-based composites. An appropriate water-binder ratio helps to form a uniformly distributed conductive network, thereby improving the self-sensing performance. A too high water-binder ratio may increase the porosity and reduce the conductive performance, while a too low water-binder ratio may cause an uneven conductive network and affect the self-sensing performance. (4) Crack control: The self-sensing performance of self-sensing engineering cement-based composites is closely related to its crack control ability. The water-binder ratio affects the crack width and number of self-sensing engineering cement-based composites. An appropriate water-binder ratio helps control the development of cracks, thereby improving the self-sensing performance of the material. (5) Durability: The water-binder ratio also affects the durability of self-sensing engineering cement-based composites. An appropriate water-binder ratio can reduce porosity and improve impermeability, thereby improving the durability of the material. (6) Conductivity: The water-binder ratio affects the dispersion of conductive carbon materials (such as carbon black) and the formation of a conductive network in self-sensing engineering cement-based composites. An appropriate water-binder ratio helps to evenly disperse the conductive carbon materials, form an effective conductive network, and improve the conductivity and self-sensing performance of the material.
[0050] The present invention ensures good dispersion of carbon black in the self-sensing engineering cement-based composite material by reasonably controlling the water-cement ratio and the combination of water reducer and dispersant, and maintains the operability and fluidity of the self-sensing engineering cement-based composite material. The entire mix design not only takes into account the conductivity and self-sensing performance of the self-sensing engineering cement-based composite material, but also ensures the optimization of mechanical properties and construction performance.
[0051] The self-sensing engineering cement-based composite material provided by the present invention includes: a conductive carbon material; the conductive carbon material includes one or more of carbon black, carbon nanotubes and graphene, and in a specific embodiment it is carbon black; the mass of the conductive carbon material is 0.5-2.0% of the mass of the cement, and in a specific embodiment it is 0.5%, 1.0%, 1.5% or 2.0%.
[0052] As an embodiment, the diameter of the carbon black is 27-40 nm, and in a specific embodiment, it is 30-35 nm, and the apparent density is 0.06-0.11 cm 3 / g, in the specific embodiment, 0.08 to 0.10 cm 3 / g, specific resistance ≤1.5Ω·m, ≤1.2Ω·m in the specific embodiment, pH value is 6-8, 7-8 in the specific embodiment, apparent specific volume is 15-18mL / g, 16-17mL / g in the specific embodiment.
[0053] Conductive carbon materials can form a conductive network in self-sensing engineered cement-based composites, thereby improving their conductivity and giving them self-sensing functions, establishing a relationship between stress or strain and the rate of change of resistivity.
[0054] After the incorporation of conductive carbon materials, the conductivity of the self-sensing engineered cement-based composite material can respond to changes in the mechanical behavior of the structure. This process can be summarized as follows: (1) During loading: Under the action of stress, the relative positions of the conductive carbon materials change, causing changes in the conductive network. Generally, larger stresses will lead to increased contact between the conductive carbon material particles and reduced resistance; while smaller stresses or deformations will lead to reduced contact between the conductive carbon material particles and increased resistance. (2) The relationship between strain and resistance: Strain (especially tensile strain) can lead to changes in the microstructure of the self-sensing engineered cement-based composite material, especially the breaking or reconnection of the conductive carbon material network, which will cause changes in resistance. By accurately measuring the change in resistance, the magnitude of the strain can be reflected, thereby enabling monitoring of the material and structure.
[0055] The present invention also provides a method for preparing the self-sensing engineering cement-based composite material described in the above technical solution, comprising the following steps:
[0056] The self-sensing engineering cement-based composite material is obtained by mixing a cementitious material, an aggregate, a conductive carbon material, an organic fiber, a water reducing agent, a dispersant and water.
[0057] As an embodiment, the mixing is: firstly dispersing the conductive carbon material in water, then adding a dispersant and a water reducer, and performing a first stirring to obtain a conductive carbon material dispersion; dry-mixing the cementitious material and the aggregate, mixing the obtained dry material and the conductive carbon material dispersion, and performing slow stirring and fast stirring in sequence, and then adding organic fibers while stirring, and repeating the slow stirring and fast stirring.
[0058] As an implementation manner, the rotation speed of the first stirring is 800-1500 rpm, and in a specific embodiment, it is 1000-1200 rpm; the time of the first stirring is 20-40 min, and in a specific embodiment, it is 30 min.
[0059] The present invention ensures that the conductive carbon material particles in the conductive carbon material dispersion can be evenly dispersed through stirring, avoiding agglomeration between the conductive carbon material particles, thereby ensuring the uniformity of the conductive carbon material dispersion; during the stirring process, the conductive carbon material particles gradually form a stable dispersion system under the joint action of water and dispersant, which ultimately helps to improve the conductivity and self-sensing performance of the self-sensing engineering cement-based composite material.
[0060] As an implementation mode, the dry mixing is performed under stirring conditions; the stirring speed is 50 to 70 rpm, and in a specific embodiment, it is 60 rpm; the dry mixing time is 2 to 5 minutes, and in a specific embodiment, it is 2 to 4 minutes.
[0061] As an implementation manner, the rotation speed of the slow stirring is 50 to 70 rpm, and in a specific embodiment, it is 60 rpm; the time of the slow stirring is 3 to 5 minutes, and in a specific embodiment, it is 4 minutes.
[0062] As an implementation mode, the rotation speed of the rapid stirring is 150-200 rpm, and in a specific embodiment, it is 180 rpm; the time of the rapid stirring is 1-2 min, and in a specific embodiment, it is 1 min.
[0063] The present invention adds organic fibers at the end to avoid agglomeration or damage during the early mixing process, ensures that the organic fibers are evenly distributed in the self-sensing engineering cement-based composite material, and reduces interference with the dispersion effects of other components such as conductive carbon materials and water reducers. In addition, evenly mixing other components before adding fibers can also help form a stable reinforcement skeleton, improve the crack control ability and tensile reinforcement effect of organic fibers, thereby ensuring the reliability and consistency of the performance of the self-sensing engineering cement-based composite material.
[0064] The present invention also provides the use of the self-sensing engineering cement-based composite material described in the above technical solution or the self-sensing engineering cement-based composite material prepared by the preparation method described in the above technical solution in structural health monitoring.
[0065] The present invention has no special limitation on the application of the self-sensing engineering cement-based composite material in structural health monitoring, and any application method well known in the art may be used.
[0066] In an embodiment of the present invention, the application is: pouring the self-sensing engineering cement-based composite material into a mold and curing it. The present invention has no special limitation on the pouring and curing process, and the pouring and curing process well known in the art can be used.
[0067] The present invention also provides a method for structural health monitoring, comprising the following steps: connecting two end electrodes of a self-sensing area in a building structure to a resistance meter with wires to obtain resistivity, and obtaining stress and / or strain according to the resistivity and the linear relationship between the resistivity and the stress and / or strain;
[0068] The raw material for preparing the self-sensing area is the self-sensing engineering cement-based composite material described in the above technical solution or the self-sensing engineering cement-based composite material prepared by the preparation method described in the above technical solution.
[0069] As an implementation mode, the building structure includes a building, a road, a bridge or a tunnel. The present invention has no special limitation on the position of the self-sensing area in the building structure, which can be determined according to actual conditions. In a bridge, the self-sensing area can be set in the negative bending moment area of the bridge, which can not only achieve the self-sensing effect, but also resist the tension exerted on the bridge to meet the bearing capacity requirements.
[0070] The self-sensing engineering cement-based composite material provided by the present invention can be used for health monitoring of infrastructure such as buildings, roads, bridges, tunnels, etc. This material can monitor the stress, strain or damage inside the structure in real time, providing the possibility for self-safety monitoring of the structure and early warning of potential brittle failure.
[0071] Figure 1 Schematic diagram of the application scenario of the self-sensing engineering cement-based composite material (CB-ECC) prepared by the present invention. Figure 1 As shown in the figure, self-sensing engineered cement-based composites are very suitable for use in negative bending moment areas of bridges due to their excellent tensile properties. This material not only meets the structural bearing capacity requirements, but also has self-sensing functions, which can monitor and respond to stress and strain changes inside the structure in real time, providing an innovative solution for bridge health monitoring and maintenance.
[0072] The present invention significantly improves the conductivity and self-sensing ability of self-sensing engineering cement-based composite materials by optimizing the content of conductive carbon materials, realizes real-time monitoring in complex stress environments such as negative bending moment areas of bridges, and solves the limitations of traditional SHM technology.
[0073] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0074] Examples 1 to 5 and Comparative Example 1
[0075] The raw material ratios of the cement-based composite materials prepared in Examples 1 to 5 and Comparative Example 1 are shown in Table 1, wherein the cement is 52.5R grade ordinary Portland cement with a particle size distribution of 1 to 300 μm;
[0076] The ore powder is S95 grade granulated blast furnace slag (GGBFS) with a density of 3100kg / m 3 , with a specific surface area of 432m 2 / kg, particle size distribution is 1-50μm;
[0077] The apparent density of silica fume is 2300kg / m 3 , particle size distribution is 1~100μm;
[0078] The particle size distribution of limestone powder is 1 to 20 μm;
[0079] The diameter of carbon black is 27-40nm, and the apparent density is 0.06-0.11cm 3 / g, specific resistance ≤1.5Ω·m, pH value is 6-8, apparent specific volume is 15-18mL / g;
[0080] The concentration of polyethylene (PE) fiber is 0.97~0.98g / cm 3 , tensile strength is 3.0GPa, tensile modulus is 116GPa, melting limit is 144-152℃, elongation at break is 1-3%, length is 18mm, diameter is 24μm; molecular weight of povidone is 40000Da;
[0081] Figure 2 The following is a flow chart of a method for preparing a self-sensing engineering cement-based composite material according to an embodiment of the present invention. The preparation method is as follows:
[0082] Disperse carbon black in water, add dispersant PVP-K30 and polycarboxylate water reducer, place on a magnetic stirrer, and stir at 1000 rpm for 30 min to obtain a carbon black dispersion;
[0083] The dry materials (cement, mineral powder, quartz sand, silica fume and limestone powder) are mixed and dry-mixed at a stirring speed of 60 rpm for 2 minutes. Subsequently, the carbon black dispersion is added, and after slowly stirring at 60 rpm for 4 minutes, the stirring speed is increased to 180 rpm and quickly stirred for 1 minute. Thereafter, polyethylene (PE) fiber is gradually added while stirring at 60 rpm within 3 minutes, and the stirring is continued at 60 rpm for 4 minutes. Finally, the speed is increased to 180 rpm again, and the mixture is quickly stirred for 1 minute to ensure uniform mixing, thereby obtaining the self-sensing engineering cement-based composite material, which is cast in a mold and cured to obtain a cast specimen;
[0084] Table 1 Raw material ratios of cement-based composite materials prepared in Examples 1 to 5 and Comparative Example 1
[0085]
[0086] Performance Testing
[0087] (1) Figure 3 The compressive strength and density diagrams of the cement-based composite materials prepared in Examples 1 to 5 and Comparative Example 1 are shown in FIG. Figure 3 It can be seen that when a small amount of carbon black (0.5% of the mass fraction of cement) is added, the compressive strength of cement-based composite materials will be improved. When more carbon black is added, the compressive strength will decrease, but the overall compressive strength can still maintain a good strength, which can meet the needs of actual engineering. When the mass fraction of cement is 1.0% or more, the density is less than 1950kg / m 3 , meeting the requirements of lightweight concrete.
[0088] (2) Figure 4 The tensile properties test diagram of the cement-based composite materials prepared in Examples 1 to 5 and Comparative Example 1, wherein (a) to (f) represent Comparative Example 1 and Examples 1 to 5, respectively, the inset is a stress-strain diagram of the tensile properties, and Table 2 is the specific values of the tensile properties.
[0089] Table 2 Tensile properties of cement-based composite materials prepared in Examples 1 to 5 and Comparative Example 1
[0090]
[0091] Depend on Figure 4 As shown in Table 2, in cement-based composites, the appropriate addition of carbon black can significantly improve its mechanical properties and strain hardening ability, but the selection of the dosage is crucial. When the carbon black dosage is 0.5% of the cement mass, its tensile strength is increased to 10.73MPa, and the tensile strain capacity reaches 9.66%, which is significantly higher than that of cement-based composites without carbon black (tensile strength 9.10MPa, tensile strain capacity 6.90%). This performance improvement is mainly due to the fact that carbon black enhances the bonding force between the fiber and the matrix, fills the micropores in the matrix, and improves the density and uniformity of the material. However, the material exhibits large stress fluctuations during the tensile process, which is related to the sensitivity of the high-strength matrix to cracks or defects.
[0092] As the amount of carbon black increases, the material properties gradually decrease. When the amount reaches 1.5% of the cement mass, the tensile strength drops to 7.51MPa and the tensile strain capacity drops to 8.00%; at 2.5% of the cement mass, the tensile strength further drops to 5.70MPa and the tensile strain capacity is only 6.73%. Excessive carbon black will agglomerate in the matrix to form stress concentration points, increase porosity, and interfere with the hydration reaction of the cement matrix, thereby reducing the density of the material and the fiber-matrix bonding properties. In addition, high amounts of carbon black also exacerbate stress fluctuations, uneven crack expansion, increased crack width, and a significant decrease in overall mechanical properties.
[0093] Therefore, the dosage of carbon black needs to be precisely controlled. Low dosage (such as 0.5%) can improve the strength and toughness of cement-based composites while taking into account their electrical conductivity, but the stress concentration sensitivity of the high-strength matrix still needs attention. Excessive carbon black will destroy the matrix structure and weaken the tensile properties. In the process of optimizing self-sensing performance, the effect of carbon black dosage on mechanical properties and crack resistance should be comprehensively considered to balance the relationship between its conductivity and structural properties.
[0094] (3) Figures 5 to 8 The compression self-sensing performance test diagrams of cement-based composite materials prepared by Comparative Example 1, Example 1, Example 3 and Example 4 are respectively, wherein (a) is CB0 dry, (b) is CB0 wet, (c) is CB0.5 dry, (d) is CB0.5 wet, (e) is CB1.5 dry, (f) is CB1.5 wet, (g) is CB2.0 dry, and (h) is CB2.0 wet. The self-sensing performance of cement-based composite materials was tested under dry and wet conditions, respectively, and samples with four carbon black dosages, namely, blank group, low conductivity group, near percolation threshold group and high conductivity group, were selected and comparatively analyzed under dry and wet conditions.
[0095] Depend on Figures 5 to 8 It can be seen that the carbon black content has a significant effect on the stability and self-sensing performance of the conductive network of cement-based composites. When no carbon black is added (CB0), the conductivity and self-sensing ability of the material are weak, and the FCR curve fluctuates greatly in a humid environment, indicating that the conductive path is easily destroyed by moisture and difficult to recover. At low carbon black content (CB0.5), the conductive network is enhanced, but the disturbance of the conductive network under humid conditions is still significant, and the improvement of self-sensing performance is limited. When the carbon black content is close to the percolation threshold (CB1.5), the self-sensing performance of the material is the best, and its FCR curve shows good linearity and stability under both dry and wet conditions. The conductive network can effectively resist the interference of humidity and stress. However, the intrusion of moisture and crack aggregation in the wet state, as well as the reconstruction of the conductive path under high stress conditions, may lead to a certain hysteresis phenomenon. Although the conductivity of high carbon black content (CB2.0) is significantly improved under dry conditions, the disturbance of moisture to the conductive network in a humid environment is more significant, the FCR curve fluctuates more, the linear relationship is weakened, and the self-sensing performance decreases instead. In summary, when the carbon black content is close to the percolation threshold (CB1.5), the best self-sensing performance can be achieved under dry and wet conditions, which provides an important basis for optimizing the conductive network stability of cement-based composites and designing high-performance self-sensing materials.
[0096] (4) Figures 9 to 12The tensile self-sensing performance test graphs of cement-based composite materials prepared by Comparative Example 1, Example 1, Example 3 and Example 4 are respectively, wherein (a) is the relationship between the resistance change rate, stress and strain and time of CB0, (b) is the strain and resistance change rate of CB0, (c) is the relationship between the resistance change rate, stress and strain and time of CB0.5, (d) is the strain and resistance change rate of CB0.5, (e) is the relationship between the resistance change rate, stress and strain and time of CB1.5, (f) is the strain and resistance change rate of CB1.5, (g) is the relationship between the resistance change rate, stress and strain and time of CB2.0, and (h) is the strain and resistance change rate of CB2.0.
[0097] Depend on Figures 9 to 12 It can be seen that in the tensile self-sensing test, the carbon black content has an Figures 9-11 The self-sensing performance and resistance change rate (FCR) of the cement were significantly affected. In the absence of carbon black (CB0), the conductive path of the material changed significantly after the crack was formed, resulting in large resistance fluctuations, showing poor self-sensing ability. After the addition of 0.5% carbon black by weight of cement, the self-sensing ability of the material was enhanced, and the resistance change rate increased, but the crack width was large, the conductive network was still unstable when the crack expanded, and the resistance fluctuated significantly. The addition of 1.5% carbon black by weight of cement made the self-sensing performance optimal, the FCR changed stably, the crack width decreased, the conductive network was more uniform, the effect of crack expansion on the conductive path was better controlled, and a strong self-sensing ability was shown. However, the carbon black addition of 2.0% by weight of cement was too high, resulting in an overly dense conductive network, a significant increase in resistance fluctuations, and an unstable self-sensing effect when the crack expanded, which ultimately led to a decrease in performance. During the stretching process, as the number of cracks increased, the conductive network gradually adapted to the distribution of the cracks, and the resistance change tended to be stable. When the carbon black content is low, the conductive network is incomplete, and the resistance fluctuates greatly when the crack expands; when the carbon black content reaches the percolation threshold (1.0-2.0%), the conductive network tends to be perfect, the resistance change is more stable and has a strong sensitivity; when the content is high, the conductive path tends to be stable, the effect of crack expansion on resistance is weakened, and poor self-sensing performance is shown. Therefore, cement-based composites with carbon black content close to the percolation threshold have the best tensile self-sensing performance. Relationship between resistance change rate and strain under tension.
[0098] Depend on Figures 9 to 12It can be seen that the carbon black content has a significant effect on the resistance change rate (FCR) and self-sensing performance of self-sensing engineering cement-based composites. At low content (0%, 0.5%), due to the less contact between carbon black particles and the incomplete conductive network, the resistance change is unstable, especially when cracks form and expand. When the carbon black content reaches the percolation threshold (1.0-2.0%), the conductive network gradually becomes complete, and the FCR shows a more obvious linear relationship with increasing strain, and is more stable. At this time, the self-sensing performance of the material is the best, and the resistance change is large and sensitive. However, at high carbon black content (such as 2.0%), due to the highly complete conductive network, the effect of crack expansion on the conductive path is weakened, and the resistance change is not large, resulting in a decrease in self-sensing performance. Therefore, the selection of carbon black content is crucial to optimizing the performance of self-sensing cement-based composites.
[0099] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A self-sensing engineering cement-based composite material, comprising an engineering cement-based composite material and a conductive carbon material; the raw materials for preparing the engineering cement-based composite material include a cementitious material, an aggregate, an organic fiber, a water reducing agent, a dispersant and water; the cementitious material includes cement, mineral powder, silica fume and limestone powder; The conductive carbon material includes one or more of carbon black, carbon nanotubes and graphene; The mass of the conductive carbon material is 0.5-2.5% of the mass of the cement.
2. The self-sensing engineering cement-based composite material according to claim 1, characterized in that: The carbon black has a diameter of 27 to 40 nm and an apparent density of 0.06 to 0.11 cm 3 / g, specific resistance ≤1.5Ω·m, pH value is 6-8, and apparent specific volume is 15-18mL / g.
3. The self-sensing engineering cement-based composite material according to claim 1, characterized in that: The organic fibers include polyester fibers and / or polyethylene fibers; the volume fraction of the organic fibers in the self-sensing engineering cement-based composite material is 1-2%; the length of the organic fibers is 15-20 mm, and the diameter is 20-25 μm.
4. The self-sensing engineering cement-based composite material according to claim 1, characterized in that: The dispersant includes one or more of polyvidone, carboxymethyl fiber and sodium polyacrylate; the amount of the dispersant added in the self-sensing engineering cement-based composite material is 0.5-1 kg / m 3 .
5. The self-sensing engineering cement-based composite material according to claim 1, characterized in that: The water reducer includes one or more of polycarboxylate water reducer, naphthylamine water reducer and lignin sulfonate water reducer; the addition amount of the water reducer in the self-sensing engineering cement-based composite material is 20-45 kg / m 3 .
6. The self-sensing engineering cement-based composite material according to claim 1, characterized in that: The mass ratio of water to gelling material is 0.16-0.24:
1.
7. The self-sensing engineering cement-based composite material according to claim 1, characterized in that: The mass ratio of the cement, mineral powder, silica fume and limestone powder is 1:1-1.1:0.2-0.3:0.1-0.15; the mass ratio of the cement and aggregate is 1:0.7-0.
8.
8. The method for preparing the self-sensing engineering cement-based composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The self-sensing engineering cement-based composite material is obtained by mixing a cementitious material, an aggregate, a conductive carbon material, an organic fiber, a water reducing agent, a dispersant and water.
9. Use of the self-sensing engineering cement-based composite material according to any one of claims 1 to 7 or the self-sensing engineering cement-based composite material prepared by the preparation method according to claim 8 in structural health monitoring.
10. A method for structural health monitoring, characterized in that: The following steps are involved: Connecting electrodes at both ends of the self-sensing area in the building structure to a resistance meter with wires to obtain resistivity, and obtaining stress and / or strain according to the resistivity and the linear relationship between the resistivity and the stress and / or strain; The raw material for preparing the self-sensing area is the self-sensing engineering cement-based composite material described in any one of claims 1 to 7 or the self-sensing engineering cement-based composite material prepared by the preparation method described in claim 8.
Citation Information
Cited By
Unfired artificial aggregate with conductivity as well as preparation and application methods of unfired artificial aggregate
CN121248168A
A conductive, non-fired artificial aggregate and its preparation and application methods
CN121248168B
Highly deformable self-sensing concrete and method for producing the same
CN122685385A